Cross-Cultural Influences on English Language: Exploring the Impact of Cross-Cultural Influences on English Language and Communication (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Language is a tool used by humans for communication with each other. Mostly, there is a great difference among linguistic forms of different countries. English has been generally applied in a range of foreign trade events as a frequent language around the world. Along with the coming of the financial economy. The paper concludes that the distinction between cultural and linguistic is often challenging to make, that a second language learning is not culturally value-free, that acculturalization and linguistic knowledge go hand in hand, and that acculturalization indicates identity shift. Globalization in different countries, institutions and among individuals promotes English language as the most important and widely used language in the world. Cultural awareness may be obtained by observing the role models in the cultural system of the language carefully. People from one community exchange their beliefs with people from another culture in cross-cultural contact. The language of cross-cultural contact is English. The research reveals the major importance, barriers and others issues related to cross-cultural communication. The main objectives of the research is to bring out that English as Foreign language will support cross cultural communication in this global arena. Empirical research method has been adopted to bring out the suggested outcomes.